Efficiency of Trichoplus (Trichoderma asperellum) as a plant growth promoter in soybean in the Cerrado field - Chagas Junior, Aloisio Freitas (2022)
The objective of this work was to evaluate the efficiency of TrichoPlus (Trichoderma asperellum) as a plant growth promoter in soybean and the productive performance in the field, in the cerrado. Two independent experiments were carried out in the municipalities of Porto Nacional (2019/2020 season) and Formoso do Araguaia (2019 season), Tocantins, Brazil. For the treatment with the TrichoPlus product, the powder formulation was used, with active principle based on T. asperellum, formulated with a minimum concentration of 2 x 108 CFU g-1, having graphite in the composition, being applied directly to the seeds (TS) before planting. Biomass, stand maintenance and productivity parameters were determined. The positive results for the characteristics of biomass, stand maintenance and productivity were evidenced in the treatment with TrichoPlus, observed in the experiments in Porto Nacional, with gains in plant biomass above 19% and an estimated increase in productivity of 8.1%. For the experiments in Formoso do Araguaia, the biomass and productivity data were higher for doses between 4 and 6 g kg-1 of seeds, with productivity gains, for these doses, of 23.6 and 16.2% in relation to the absolute witness, respectively. Soybean inoculation, in the Porto Nacional and Formoso do Araguaia regions, with the TrichoPlus product promoted an increase in biomass characteristics, efficiency in stand maintenance and productivity, proving its efficiency in promoting plant growth and, consequently, in productivity.